Predictive Power of Mindset in Determining the Pattern of Goal Orientation among Hashemite University students - Ghbari, Thaer; Al Sarayreh, Asmaa (Dirasat: Educational Sciences, 2021)
The current study aims at detecting the type of mindset prevailing among a sample of the Hashemite University students and the type of goal orientation adopted by them, in addition to the predictive power of the mindset on goal orientation among the students. To achieve the objectives of the study, the descriptive correlative approach was used. Data was collected from 214 students from the Hashemite University using two scales, the 16-item goal Orientation Scale (Button, Mathieu, & Zajac, 1996) which measures two goal orientations styles (learning objectives versus performance objectives). To measure the (progressive versus protective mindset), 28-item mindsets scale, was developed by the researcher. The results showed that the students possess the two mindsets, but they possess the progressive mindset in the first place, and they also possess the two types of goals, but they possess the learning goals in the first place as well. The results also showed that the mindset is a good predictor in determining the type of goal orientations of students. A progressive mindset is consistent with learning goals, and a preventive mindset is consistent with performance goals. The study also emphasized the importance of goal orientations to maintain students' inclination towards learning and mastery. The researcher recommends conducting more studies on mindset due to the scarcity of Arabic studies that dealt with it.